2007
DOI: 10.1042/bj20070811
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal region of ABC50 interacts with eukaryotic initiation factor eIF2 and is a target for regulatory phosphorylation by CK2

Abstract: ABC50 is an ABC (ATP-binding cassette) protein which, unlike most ABC proteins, lacks membrane-spanning domains. ABC50 interacts with eIF2 (eukaryotic initiation factor 2), a protein that plays a key role in translation initiation and in its control, and in regulation of ribosomes. Here, we establish that the interaction of ABC50 with eIF2 involves features in the N-terminal domain of ABC50, the region of ABC50 that differs most markedly from other ABC proteins. This region also shows no apparent similarity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…Our recent data showed that the N terminus of ABC50 was sufficient for its interaction with eIF2 (21). In contrast, the N terminus of ABC50 is not sufficient to mediate association with ribosomes, either NBD1 or NBD2 also being required (21).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our recent data showed that the N terminus of ABC50 was sufficient for its interaction with eIF2 (21). In contrast, the N terminus of ABC50 is not sufficient to mediate association with ribosomes, either NBD1 or NBD2 also being required (21).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work (2,21) showed that ABC50 interacts with eIF2 and suggested that ABC50 promoted the association of eIF2 with initiator methionyl-tRNA in vitro. This implied that ABC50 probably played a role in mRNA translation, probably at the initiation stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations